Enrichment and Characterisation of Cellulose Degrading Bacteria - Golwalkar, Sucheta; Khatri, Farida (Defence Life Science Journal, 2023)
In the current research, a total of 10 bacterial isolates have been collected from municipal waste, vegetable waste, a dumping ground, a rice field, termite waste, cotton dyeing industry waste, forest waste, the soil under a coconut tree, dead decomposed plant waste, and sewage waste.Using soluble carboxy methyl cellulose degradation assays, the 10 bacterial strains have been isolated and examined for cellulolytic activity. In one percentage CMC agar medium, four strains, namely C9D, C9E, C9C, and C9B, efficiently digested cellulose, with a cellulolytic index of 35 mm, 25 mm, 17 mm, and 18 mm, respectively. The appearance of a clear zone was utilised to estimate cellulolytic activity. High-cellulolytic-activity isolates were identified up to the genus level.